Peningkatan Literasi Digital Kesehatan bagi Masyarakat dalam Mengakses Informasi Medis yang Akurat melalui Pemanfaatan Sistem Informasi Kesehatan - Putri, Santy Irene; Widiyanto, Aris; Ummah, Wiqodatul; Supriyono, Nisa'i Daramita; Prisusanti, Retno Dewi; Akbar, Prima Soultoni; Widiatrilupi, Raden Maria Veronika; Purwanti, Anik; Abdullah, Ikhwan; Wardoyo, Puspo; Gamar, No’o (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The use of digital technology in the health sector is increasing, but public health digital literacy is still relatively low. This affects the public's ability to access accurate and reliable medical information. This service activity aims to improve public health digital literacy in using health information systems to find the right medical information. This program is carried out with preparation stages which include socialization to the community as well as the preparation of training materials and tools. The implementation of the activity consisted of a theory session by introducing digital technology and health information systems, followed by a practicum session where participants were trained using health applications and digital medical platforms. The evaluation was conducted by collecting feedback from participants to assess their improvement in knowledge and skills in accessing medical information digitally. The results of the evaluation showed that the majority of participants felt more confident in using technology to obtain accurate medical information after participating in this training.